Food processing technology - Fellows, P.J. (Woodhead Publishing, 2011)
This new edition has been thoroughly updated and considerably expanded to take account of the advances in technology. Each chapter describes the theoretical and practical aspects of the unit operation including the formula required for calculation of processing parameters, sample problems and the effects on sensory characteristics, and nutritional properties of selected foods.